DISTRIBUTION OF GLEASON SCO¬RE IN PROSTATE ZONES AMONG PROSTATIC CANCER PATIENTS - Jaya, Indra; Sugandi, Suwandi; Yantisetiasti, Anglita; Hernowo, Betthy S. S. (Indonesian Journal of Urology, 2012)
Objective: To analyze the distribution features of Gleason score in the different prostate zones. Material & Method: Twenty paraffin block specimens of radical prostatectomy were analyzed looking for Gleason score distribution in each zone. Specimens were stained with Hematoxilin Eosin. Results: Among the 20 cancers, 16 (80%) specimens had more than one focus. Most foci were found in peripheral zone (95%), only one specimen contained foci solely found in transitional zone. More than half (55%) prostate specimens contain three different Gleason grades. Only one specimen contained a single grade. Conclusion: Our results confirm the heterogeneous, multifocal, and multizonal nature of prostate carcinomas. Most specimens had more than one tumor focus, with predominant location in the peripheral zone. Almost all transition zone foci were found concomitantly with peripheral zone foci. Keywords: Prostate cancer, prostate zones, Gleason score.